The role of somatic hypermutation in the generation of pathogenic antibodies in SLE - Kristin, Schröder; Herrmann, Martin; Winkler, Thomas (Autoimmunity, 2013)
The formation of antibodies against double-stranded (ds)DNA is considered to be the serologic hallmark of systemic lupus erythematosus (SLE) and anti-dsDNA antibodies play an important role in the pathogenesis of the disease. Anti-dsDNA antibodies from lupus mice and SLE patients arise by somatic mutation. Importantly, autoantibodies in which somatic mutations have been reverted to germ-line V regions did not show any measurable autoreactivity, suggesting that anti-dsDNA autoantibodies develop from non-autoreactive B-cells by somatic hypermutation, presumably during the germinal center reaction. As the random nature of somatic hypermutation will inevitably create autoreactive B cells, self-tolerance checkpoints at the postmutational stage of B cell differentiation have to exist that normally prevent the induction of pathogenic anti-dsDNA specificities. This review summarizes the proposed mechanisms for the generation of anti-dsDNA in murine lupus and in SLE patients. © Informa UK, Ltd.
Keywords: Anti-DNA antibodies; Germinal center; Somatic mutation; Systemic lupus erythematosus